Postoperative Pain in Children - Ümit Akkemik (Genel Tıp Dergisi)
Postoperative pain is an acute pain that starts with surgical trauma and gradually decreases with healing of the tissue. The mechanism of pain perception in the pediatric population is different and poorly understood. Difficulties in defining and grading pain in pediatric patients also complicate treatment. Postoperative pain management in children should be planned with a multidisciplinary and multimodal approach. In this article, it is aimed to review up-to-date information on pediatric postoperative pain management.